2001
DOI: 10.1128/jcm.39.10.3633-3636.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Vitek Gram-Positive Susceptibility 106 Card, the MRSA-Screen Latex Agglutination Test, and mecA Analysis for Detecting Oxacillin Resistance in a Geographically Diverse Collection of Clinical Isolates of Coagulase-Negative Staphylococci

Abstract: The Vitek automated susceptibility testing system with a modified gram-positive susceptibility (GPS) 106 card (bioMerieux Vitek, Inc., Hazelwood. Mo.) and a rapid slide latex agglutination test (MRSA-Screen test; Denka Seiken Co., Ltd., Tokyo, Japan) were evaluated for their abilities to detect oxacillin resistance in coagulase-negative staphylococci (CoNS). The reference broth microdilution method and the detection of the mecA gene by PCR ("gold standard" reference result) were used to compare the results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…In Brazil, a multicenter study showed that methicillin resistance was observed in 87.7% of CoNS isolated from bloodstream infections (Sader et al 1999). The accurate detection of methicillin resistance among CoNS isolates in the clinical laboratory is important to guide therapy and to promote the correct use of glycopeptides (Hussain et al 1998, Yamazumi et al 2001.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, a multicenter study showed that methicillin resistance was observed in 87.7% of CoNS isolated from bloodstream infections (Sader et al 1999). The accurate detection of methicillin resistance among CoNS isolates in the clinical laboratory is important to guide therapy and to promote the correct use of glycopeptides (Hussain et al 1998, Yamazumi et al 2001.…”
mentioning
confidence: 99%
“…In Brazil, a multicenter study showed that methicillin resistance was observed in 87.7% of CoNS isolated from bloodstream infections (Sader et al 1999). The accurate detection of methicillin resistance among CoNS isolates in the clinical laboratory is important to guide therapy and to promote the correct use of glycopeptides (Hussain et al 1998, Yamazumi et al 2001.This work was performed to evaluate the accuracy of two automated systems in the identification of species and determination of methicillin resistance, considering as gold standard the conventional biochemical tests and the characterization of mecA gene by polymerase chain reaction (PCR), respectively. …”
mentioning
confidence: 99%
“…A second function of antibiotic susceptibility tests is to monitor the effectiveness of therapy is compromised by the potential development of tolerance or resistance to that component [1][2][3][4][5]. It is true for all agents used in the treatment of bacterial, fungal, parasitic, and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been superseded by the introduction of selective agar cultivation methods and latex agglutination tests for the specific detection of the product of the mecA gene, penicillin-binding protein 2a. Most of these tests have been evaluated in different studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Sensitivity and specificity for agar cultivation ranged from 40 to 98% and 80 to 100%, respectively.…”
Section: Phenotypic Detection and Identification Of Mrsamentioning
confidence: 99%